DISTRIBUSI DAN MARGIN PEMASARAN PRODUK OLAHAN OPAK SINGKONG DI KOTA KENDARI - Hartatia Nur; La Ode Arfan Dedu; Normal Bivariant Padangaran (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2024)
Marketing is a crucial aspect of the agribusiness system. One potential agroindustry in Kendari City is cassava chips processing. Sampling was conducted using the snowball sampling method, identifying, selecting, and sampling respondents totaling 30 individuals, with the majority being cassava chip entrepreneurs who are housewives. These retail traders prefer direct marketing channels to reach more consumers and facilitate easier purchase of cassava chip products without having to buy directly from the production site. For marketing efficiency, results found for marketing channel I were 0.15%, while for channel II it was 7.26%. This approach also benefits retailers who obtain cassava chip products without going through wholesalers. In practice, there will be cost and revenue calculations incurred by both producers and marketing institutions involved, resulting in different outcomes and creating marketing margins. The larger the marketing margin, the less efficient the marketing activities become. This research aims to determine the distribution of marketing, the size of marketing margins, and the proportion of the price received by cassava chip producers (producer's share) from the retail price. The findings of this research are expected to provide benefits and increase income for the marketing institutions involved in promoting cassava chip products in Kendari City.